Development and improvement of the simulation of woody bioenergy crops in the Soil and Water Assessment Tool (SWAT). (December 2019) - Guo, Tian; Engel, Bernard A.; Shao, Gang; Arnold, Jeffrey G.; Srinivasan, Raghavan; Kiniry, James R.
Abstract: Quantifying Populus growth and the impacts on hydrology and water quality are important should it be widely planted. Soil and Water Assessment Tool (SWAT) tree growth algorithms and parameters for hybrid poplar in Midwestern US and cottonwood in Southern US were improved. Tree growth representation led to SWAT2012 code changes including a new leaf area parameter (TREED), new leaf area index algorithm, and leaf biomass algorithm. Simulated hybrid poplar LAI and aboveground woody biomass (PBIAS : 34 - 5%, NSE: 0.51–0.99, and R 2 : 0.72–0.99), and cottonwood aboveground biomass, runoff, sediment, and nitrate-N (PBIAS : 39 - 11%, NSE: 0.86–0.99, and R 2 : 0.93–0.99) from the modified SWAT were satisfactory. Improved algorithms, and parameter values and potential ranges for Populus were reasonable. Thus, the modified SWAT can be used for Populus biofeedstock production modeling and hydrologic and water quality response to its growth. Highlights: We improved tree seasonal maximum LAI and dropping leaves weight simulation in SWAT. We modified SWAT to simulate LAI and biomass yields for juvenile and mature Populus. The modified SWAT can model biofeedstock production for Populus. The modified SWAT can model water quantity and quality response to tree growth. The improved algorithms and parameters are useful for other process based models.